2013
DOI: 10.1002/suco.201300003
|View full text |Cite
|
Sign up to set email alerts
|

Design recommendations for interface shear transfer in fib Model Code 2010

Abstract: Interface shear transfer between differently aged concretes is a topic that crops up frequently and in different situations in structural design. In the fib Model Code for Concrete Structures 2010 the fundamental basics of concrete‐to‐concrete load transfer are given in section 6.3 and the corresponding design rules in 7.3.3.6. The different potential mechanisms contributing to the shear resistance along the interface, i.e. adhesive bond, aggregate interlock, friction and dowel action, are thus combined and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(62 citation statements)
references
References 10 publications
1
57
0
4
Order By: Relevance
“…The above results were contradicted by the general agreement for the concrete-to-concrete interface under direct-shear test (Randl 2013;Niwa et al 2016), which concluded that as the degree of roughness of a particular surface increases; the ultimate capacity also increases significantly. The different results in this study can be explained as follows.…”
Section: Effect Of Surface Roughnessmentioning
confidence: 90%
See 1 more Smart Citation
“…The above results were contradicted by the general agreement for the concrete-to-concrete interface under direct-shear test (Randl 2013;Niwa et al 2016), which concluded that as the degree of roughness of a particular surface increases; the ultimate capacity also increases significantly. The different results in this study can be explained as follows.…”
Section: Effect Of Surface Roughnessmentioning
confidence: 90%
“…Since the experimental failure mode was a shear failure at the interface, the experimental shear capacities were compared with predicted shear capacities using JSCE Specification (2007), AASHTO (2007), and fib Model Code 2010(2013. The shear capacity predicted by these guidelines was considered without partial safety factors.…”
Section: Predicted Shear Capacitymentioning
confidence: 99%
“…A total of 207 push-off specimens (including 133 rough construction joints, and 74 smooth construction joints) compiled from different sources in the literature [4,5,11,[17][18][19][20][21][22][23][24][25] were used to examine the reliability and safety of the code equations and mechanical equations with regard to the effect of the different parameters on the shear friction strength of the construction joints. e distribution of the different parameters in the database is shown in Figure 1.…”
Section: Database Of Push-off Specimens With Construction Jointsmentioning
confidence: 99%
“…e crack propagation and failure plane of a member governed by shear friction are concentrated on the interfacial shear plane [1][2][3]. Despite the fact that the mechanism of shear friction is considerably more complex than that of conventional friction [4,5], the ACI 318-14 provision [6] simply considers that applied shear is mostly transferred by the resistance generated from the friction between the two sliding faces and a clamping force. e clamping force is induced by the transverse reinforcement crossing the interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation